A Pseudo‐Model Strategy Combining Experiment and Model to Investigate the Targeting Efficiency of Injected Magnetic Nanoparticles as Therapeutics Carriers1. Issue 10 (2nd April 2015) - Liu, Yanping; Xue, Yanan; Yu, Bo; Long, Sihui; Luo, Xiaogang; Cai, Ning; Yu, Faquan
<x xml:space="preserve">Abstract</x> Magnetic drug targeting (MDT) with the attachment of therapeutics on magnetizable particles to position them to target locations for the enhancement of targeting efficiency (TE) would allow better treatment of not only cancer but other diseases. However, the TE is low usually. The prediction of TE is necessary but difficult in whether theoretical or experimental aspect. A pseudo‐model strategy dependent on both the experiment and model was developed to this end. Two processes of blood circulation clearance and targeting magnetic migration were abstracted to depict the fate of in vivo injected magnetic particles. The pseudo‐model is to calculate TE in terms of two variables, or the half lives representing the respective characteristic time for the two processes, which can be conveniently determined experimentally. Two magnetic particles of different mobility were prepared for the in vitro assessment of the model. The experimental results verified the reliability of the model. An optimal targeting time was proposed to guide the targeting process. The model also provides a clue that the TE cannot be high. The strategy can determine TE readily by broad choice of these parameters.